Substitusi ransum jadi dengan roti afkir terhadap performa burung puyuh (Coturnix coturnix japonica) umur starter sampai awal bertelur - Susan E Lumban Gaol; Lisnawaty Silitonga; Iis Yuanita (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2015)
This study was conducted to evaluate the effect of substitution of commercial feed with expired bread within a certain level on the performance of quail. This study used a completely randomized design (CRD) and Analysis of Varian (ANOVA), if the obtained data showed significant differences then tested further using HSD test α = 5%. Fifty four (54) DOQ (day old quail) were grouped into three (3) treatments and six (6) replication, each replication, consisted of 3(three) DOQ. The treatments were P0 (complete feed or control), P1 (85% complete feed + 15% expired bread) and P2 (complete feed 70% + 30% expired bread). The feed were given twice a day with increasing portion every week while drink were given adlibitum and was carried out for 42 days. Results showed no signification differences on all parameters observed, those parameter are feed consumption, body weight gain, feed conversion and IOFC (income over feed cost). Giving expired bread at 15% and 30% within commercial feed, did not effect on feed intake, body weight gain and feed conversion. But the substitution of expired bread up to 30% within commercial feed can still be done with no negative effect on the performance of quail in addition, it can provide greater economic benefit. Key words : Expired bread, performance, quai